Design and analysis microstrip antenna with reflector to enhancement gain for wireless communication - ِAli Khalid Jassim; Raad H. Thaher (Bulletin of Electrical Engineering and Informatics, 2020)
In this paper is presented the good solution to enhancement gain by using physical plane plate reflector with optimum distance by a reflector was used with the antenna and using a sweep parameter for the distance at which the reflector was placed at (, we found the best distance is when selected the bandwidth is 28GHz where . The gain at the bandwidth in 28GHz was improved from (5.48, 6.78, and 7.83) dB to 11.53 dB, while the gain without a reflector is 7.1 dB. The simulation results were obtained using CST which was more consistent with the practical results.